Ekoefisiensi Penggunaan Input Produksi pada Usaha Pembibitan Alpukat (Persea americana Mill): Studi Kasus di CV. Mitra Tani, Kabupaten Sleman, Yogyakarta - Farhan Mahbubi; Meita Puspa Dewi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Rising demand for quality avocado seedlings intensifies input use in nursery businesses, yet eco-efficiency analysis at the input level remains underexplored in Indonesian horticultural agribusiness literature. This study aims to: (1) identify the types and quantities of production inputs used at CV. Mitra Tani; (2) measure economic feasibility and eco-efficiency of measurable inputs (seedlings, labor, and water); and (3) identify factors influencing eco-efficiency levels. A quantitative descriptive case study design was employed, with primary data collected through structured interviews with the nursery owner on February - April 2026. Eco-efficiency was calculated using a simple ratio approach, while economic feasibility was assessed using the R/C Ratio. Results show that labor cost dominates the cost structure at 96% of total production, reflecting the labor-intensive nature of manual grafting. The R/C Ratio of 2.0 confirms economic feasibility and positions CV Mitra Tani competitively among similar enterprises in Central Java. Seedling eco-efficiency reached IDR 20,000/stem, labor eco-efficiency 3.47 stems/workday, and water eco-efficiency 0.0003 stems/liter. Three structural factors constrain eco-efficiency: limited specialized labor expertise, high urban wage costs, and declining market purchasing power. Eco-efficiency improvements can be achieved without additional inputs through grafting procedure standardization and targeted human resource development. This study contributes an empirical framework for input-level eco-efficiency analysis in horticultural nursery agribusiness.